Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1136/jnnp-2011-301695
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DaTscan SPECT imaging on clinical management, diagnosis, confidence of diagnosis, quality of life, health resource use and safety in patients with clinically uncertain parkinsonian syndromes: a prospective 1-year follow-up of an open-label controlled study

Abstract: DaTscan had a significant impact on clinical management, diagnosis and CoD in patients with CUPS. DaTscan is safe and well tolerated, and is a useful adjunct to differentiate a diagnosis of CUPS. Trial registration number http://ClinicalTrials.gov Identifier: NCT00382967.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 38 publications
8
70
1
2
Order By: Relevance
“…The 5 studies have been published (1)(2)(3)(4)(5)(6)(7)(8), including the inclusion/ exclusion criteria. Table 1 provides a summary of the details of the studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5 studies have been published (1)(2)(3)(4)(5)(6)(7)(8), including the inclusion/ exclusion criteria. Table 1 provides a summary of the details of the studies.…”
Section: Methodsmentioning
confidence: 99%
“…Each g camera system was capable of SPECT acquisition and reconstruction to produce transverse slices, including a clear visualization of the striatum (i.e., the head of the caudate nucleus and putamen). Images were acquired within 3-6 h after radiotracer injection (1)(2)(3)(4)(5)(6)(7)(8). Images were read on-site or by 3 or 5 BIE readers and classified as normal (SDD absent) or abnormal (SDD present) (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent prospective multicentric studies have looked at the impact of 123 I-FP-CIT SPECT on clinically uncertain PS and demonstrated that for the subgroup of patients who underwent the scanning procedure, medication was changed at a significantly earlier time point and there was significantly greater confidence in the diagnosis 4 wk, 12 wk, and 1 y after the initial diagnosis. Inclusion of imaging, therefore, has had a significant impact on clinical management, diagnosis, and diagnostic confidence in a patient population with uncertain PS (82).…”
Section: Economic Considerationsmentioning
confidence: 99%
“…Studies show that DaTSCAN improves confidence in diagnosis and management in clinically uncertain parkinsonian syndromes. 5 Cancer risk from any scan cannot be ignored. The 1 in 7,500 possible cancer risk 1 has to be compared to the greater chance of psychological trauma of a falsepositive PD diagnosis or the functional disability that may result from a missed PD diagnosis.…”
Section: Megan Alcauskas MD and Robert C Griggs Mdmentioning
confidence: 99%